2014
DOI: 10.1038/jcbfm.2014.3
|View full text |Cite
|
Sign up to set email alerts
|

Regional Neurovascular Coupling and Cognitive Performance in Those with Low Blood Pressure Secondary to High-Level Spinal Cord Injury: Improved by Alpha-1 Agonist Midodrine Hydrochloride

Abstract: Individuals with high-level spinal cord injury (SCI) experience low blood pressure (BP) and cognitive impairments. Such dysfunction may be mediated in part by impaired neurovascular coupling (NVC) (i.e., cerebral blood flow responses to neurologic demand). Ten individuals with SCI 4T6 spinal segment, and 10 age-and sex-matched controls were assessed for beat-by-beat BP, as well as middle and posterior cerebral artery blood flow velocity (MCAv, PCAv) in response to a NVC test. Tests were repeated in SCI after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 46 publications
0
80
2
1
Order By: Relevance
“…For example, chronic hypotension depresses cognitive activity and resting CBF, which is directly mediated by neurovascular coupling. 72,80 Conversely, cognitive activity can be improved with pharmacological treatment of hypotension, through improvements in neurovascular coupling; 52,81 82 In order to increase the clinical utility of neurovascular coupling as an end-point treatment target, there is a need for an automated and standardized protocol for analysis, which produces interpretable metrics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, chronic hypotension depresses cognitive activity and resting CBF, which is directly mediated by neurovascular coupling. 72,80 Conversely, cognitive activity can be improved with pharmacological treatment of hypotension, through improvements in neurovascular coupling; 52,81 82 In order to increase the clinical utility of neurovascular coupling as an end-point treatment target, there is a need for an automated and standardized protocol for analysis, which produces interpretable metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Both the P1 and P2 segments have been utilized with similar results, however a consistent segment should be maintained throughout a given study. 52,55,73,92,93 Lastly, often only the posterior window is suitable for insonating intracranial vessels in the elderly, due to skull thickening with advancing age. 94 Some studies have reported that 10À15% of individuals will have inadequate windows for insonating intracranial cerebral vessels; 95 as such, it may be advantageous to utilize other techniques such as NIRS (see next section) in addition to TCD for studies in the elderly or those with related cerebrovascular pathology.…”
Section: Transcranial Dopplermentioning
confidence: 99%
See 1 more Smart Citation
“…22,49 Our data support the notion that not only is MFV reduced in persons with SCI compared to AB controls, but SFV and DFV are also significantly lower. These findings indicate persistent cerebral hypoperfusion throughout the entire cardiac cycle in hypotensive individuals with chronic SCI, which may contribute to the increased incidence of cerebrovascular disease 50 and ischemic stroke, 18 as well as cognitive deficits, 23,51,52 and impairment in health related QOL. 10 …”
Section: Discussionmentioning
confidence: 86%
“…17 Further, an increased incidence of hemorrhagic and ischemic stroke was noted in the Taiwanese SCI population (n=2806) compared to propensity-score matched controls (n = 28,060), which the authors speculate may relate to fluctuations in BP. 18 Transcranial Doppler ultrasound (TCD) technology has been used to non-invasively assess CBF velocity (CBFv) at the middle cerebral artery (MCA) [19][20][21][22][23][24] and the posterior cerebral arteries 23,24 in the SCI population. From TCD recordings of the MCA, reduced resting CBFv has been documented in persons with SCI 22,25 and altered static and dynamic autoregulation compared to controls is reported.…”
Section: Introductionmentioning
confidence: 99%